2021
DOI: 10.3390/cancers13122953
|View full text |Cite
|
Sign up to set email alerts
|

CUT Domain Proteins in DNA Repair and Cancer

Abstract: Recent studies revealed that CUT domains function as accessory factors that accelerate DNA repair by stimulating the enzymatic activities of the base excision repair enzymes OGG1, APE1, and DNA pol β. Strikingly, the role of CUT domain proteins in DNA repair is exploited by cancer cells to facilitate their survival. Cancer cells in which the RAS pathway is activated produce an excess of reactive oxygen species (ROS) which, if not counterbalanced by increased production of antioxidants, causes sustained oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 103 publications
(212 reference statements)
0
11
0
Order By: Relevance
“…As an upstream component of the Ras-MAPK pathway, the EGFR ligand EREG is a particularly interesting candidate for further studies of the mechanisms of NS-CM. The observed increase in CUX2 expression may also be related to Ras-MAPK hyperactivation, as CUT domain proteins have been shown to accelerate DNA repair and prevent senescence in cells with elevated reactive oxygen species (ROS) levels because of increased Ras signaling ( Ramdzan et al., 2014 , 2021 ). We also found high multinucleation in NS-CM LV cardiomyocytes, which was recapitulated in PTPN11 N308S/+ iPSC-CMs.…”
Section: Discussionmentioning
confidence: 99%
“…As an upstream component of the Ras-MAPK pathway, the EGFR ligand EREG is a particularly interesting candidate for further studies of the mechanisms of NS-CM. The observed increase in CUX2 expression may also be related to Ras-MAPK hyperactivation, as CUT domain proteins have been shown to accelerate DNA repair and prevent senescence in cells with elevated reactive oxygen species (ROS) levels because of increased Ras signaling ( Ramdzan et al., 2014 , 2021 ). We also found high multinucleation in NS-CM LV cardiomyocytes, which was recapitulated in PTPN11 N308S/+ iPSC-CMs.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several BER enzymes including Pol β, APE1 and FEN1 were found to be overexpressed in multiple cancers ( 16–24 ). Likewise, aberrant or increased expression of the BER accessory factors CUX1, CUX2 and SATB1 were reported in multiple tumours and cancer cell lines (reviewed in ( 25 )). Notably, knockdown of these BER accessory factors was shown to be synthetic lethal in cell lines that exhibit high levels of reactive oxygen species ( 26–30 ).…”
Section: Introductionmentioning
confidence: 97%
“…The antimalaria mechanism of ART, which includes iron accumulation and ROS production, has led researchers to wonder whether this approach applies to antitumor therapy [ 71 , 73 , 74 ]. Many studies have demonstrated that tumor tissues exhibit increased levels of ROS than normal tissues [ 109 111 ]. However, under sustained oxidative stress, tumor cells become well-adapted to such stress through a set of mechanisms, and they often have defects in cell death executioner mechanisms, which is one of the main causes of therapy resistance.…”
Section: Discussionmentioning
confidence: 99%